Kasundu dan Pengobatannya pada Masyarakat Muna di Desa Kusambi Kecamatan Kusambi Kabupaten Muna Barat - Hamnianti Hamnianti; Wa Ode Sitti Hafsah; Rahmat Sewa Suraya (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2022)
Kasundu traditional medicine is a disease caused by ancestral spirits or dead people, which cannot be treated through medical personnel but only with traditional medicine. The purpose of the study was to determine the community's knowledge of kasundu and its treatment and to describe the process and meaning of traditional kasundu medicine. The method used in this research is qualitative research with data collection through observation, in-depth interviews, and documentation. The results showed that the public's knowledge of the causes and effects of kasundu and its treatment. Characteristics of kasundu pain are high fever, headache, vomiting, thrashing or crying unstoppable (children sufferers). Usually the disease will feel more painful in the afternoon or midnight. According to the knowledge of the people of Kusambi Village, kasundu treatment cannot be cured through medical personnel but by using traditional medicine. The traditional kasundu treatment is divided into two parts, namely the pamole stage and the kafoampe stage. Each section has stages consisting of the preparation, implementation and finalitation.